Pengaruh pengelolaan keberagaman SDM terhadap kinerja karyawan Grand Hotel Jambi - Hidayatullah, Shofi; Sumarni, Sumarni; Rosita, Sry (Jurnal Dinamika Manajemen, 2020)
This study aims to obtain an overview of the diversity of human resources and employee performance at the Grand Hotel Jambi, as well as to see the effect of managing the diversity of human resources on employee performance at the Grand Hotel Jambi. This research is included in causality research, which is looking for explanations in the form of a cause-effect relationship between several concepts or several variables or several strategies developed in management. To test the hypothesis using a linear regression equation. The results of the descriptive study explain that the management of the diversity of human resources at Grand Hotel Jambi has been going well. Then for employee performance it is known that the employee performance at the Grand Hotel Jambi is categorized as quite high. Furthermore, based on hypothesis testing, it can be concluded that the management of human resource diversity has an effect on employee performance. This explains that if an organization is able to manage the diversity that exists, then this will be able to improve employee performance in an organization.